Assessment of Supraeruption of Teeth Affecting Prosthodontics Rehabilitation in Different Segments of Opposing Arch: Assessment of supraeruption of teeth - Khan, Muhammad Sartaj; Raza, Muhammad; Khan, Hassan; Zubair, Naila; Ur Rahman, Ejaz; Afridi, Saima (Pakistan Journal of Health Sciences, 2022)
Loss of vertical space due to supraeruption of teeth in opposing arch can make it difficult to replace missing teeth with implants, removable or fixed partial dentures. Objective: In the current study, we sought to evaluate and quantify the quantity of supraeruption of teeth in different segments of arch during prosthodontics rehabilitation with different prostheses. Methods: This cross-sectional study included 140 subjects with unopposed teeth from prosthodontics department. Data were collected by pre-structured proforma. Amount of supraeruption were recorded in millimeters on dental casts after obtaining impressions. Teeth involved in supraeruption like molars and others on right/ left side in either maxillary / mandibular arch, were noted from study casts and were assessed. Data were analyzed using (SPSS version 20). Results: For the study, 140 individuals in total were selected (54 males and 86 females). This study observed dental caries as the main cause of tooth loss. Mean age of patients were 43 years. Mean super-eruption values for subjects were 2.22mm with standard deviation of 0.66mm. More number of supraerupted teeth were found in unopposed maxillary arch than the mandibular. Highest frequency of super-eruption was found in molars areas and on right side of the arch. Conclusions: It was concluded that unopposed teeth lead to over-eruption of antagonists. Differences were recorded between sites, type and status of supra-eruption. Current study observed that highest ratio of super-eruption recorded in maxillary arch, in molar region and on the right side of arch.